An Efficient and Green Synthesis of Fluorine Containing Benzo[a]xanthen-11(12H)-ones and Evaluation of their Anticancer Activity - Sumalatha, J.; Sreedevi, A.; Rani, C. Radha (Asian Journal of Chemistry, 2020)
A facile and an efficient procedure has been developed by one-pot condensation of naphthalene-diols, fluoro substituted benzaldehydes and cyclic 1,3-dicarbonyl compounds for the synthesis of fluorine containing benzo[a]xanthen-11(12H)-ones under the catalyst and solvent-free conditions. All the synthesized compounds were characterized by IR, NMR (1H & 13C) and mass spectrometry. Several advantages offer the present approach, such as, shorter reaction time, low cost, anticipation of toxic solvents and catalyst, higher yield of products and durability of substrate range. On the other hand, anticancer activity was also performed for the title compounds which demonstrated a significant activity on selected cancer cell lines.